Regional anesthesia in faciomaxillary and oral surgery - Manimaran Kanakaraj; N Shanmugasundaram; M Chandramohan; R Kannan; S Mahendra Perumal; J Nagendran (Wolters Kluwer Medknow Publications, 2012)
Faciomaxillary and oral surgical procedures are frequently done under local anesthesia. Only few techniques are used widely in these areas in spite of the numerous blocks available. Knowledge about these techniques could encourage use of these techniques for the benefit of patients and operators' comfort. Leaving aside the commonly used intraoral anesthetic technique by faciomaxillary and dental surgeons, focus is given on regional blocks of extraoral route, like maxillary block, mandibular block, superficial cervical plexus block, forehead and scalp block, trigeminal nerve block, sphenopalatine nerve block, and they are discussed with their indications and technical details involved in administering them. Advantages of using the regional blocks over general anesthesia and multiple pricks include reduced dosage and number of needle pricks. Pediatric considerations like prolonged duration of anesthesia and wider area of action for regional blocks warrant that they should be used with caution.